2022
DOI: 10.1002/adfm.202202737
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Overpotential of Aprotic Li‐CO2 Batteries with the In‐Plane Alloy Structure in Ultrathin 2D Ru‐Based Nanosheets

Abstract: The aprotic Li-CO 2 battery is emerging as a promising energy storage technology with the capability of CO 2 fixation and conversion. However, its practical applications are still impeded by the large overpotential. Herein, the general synthesis of a series of ultrathin 2D Ru-M (M = Co, Ni, and Cu) nanosheets by a facile one-pot solvothermal method is reported. As a proofof-concept application, the representative RuCo nanosheets are used as the cathode catalysts for Li-CO 2 batteries, which demonstrate a low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 73 publications
0
40
0
Order By: Relevance
“…4b , the battery exhibits robust cycle stability over 400 cycles. The discharge voltage (3.01 V) and energy efficiency (75.4%) of this work are the best results among the reported solid or liquid catalysts during full discharge-recharge process at the current density of 100 mA g −1 25 , 28 , 56 61 (Fig. 4c ).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…4b , the battery exhibits robust cycle stability over 400 cycles. The discharge voltage (3.01 V) and energy efficiency (75.4%) of this work are the best results among the reported solid or liquid catalysts during full discharge-recharge process at the current density of 100 mA g −1 25 , 28 , 56 61 (Fig. 4c ).…”
Section: Resultsmentioning
confidence: 60%
“…b Cyclic performance of the Li–CO 2 battery with a Cu(I) RM-based electrolyte and a Ru@Super P cathode under a fixed specific capacity of 1000 mAh g −1 at a current density of 200 mA g −1 . c Comparison of discharge voltage and energy efficiency with other reported catalysts for Li–CO 2 batteries in recent reports 25 , 28 , 56 61 . d Schematic of the synergetic effect of Cu(I) RM and Ru catalysts for the Li–CO 2 battery system.…”
Section: Resultsmentioning
confidence: 99%
“…30g–j). 532 As a representative, fine structure investigations suggested that the obtained 2D RuCo nanosheets endowed a lower Ru–Ru coordination number but a relatively higher Ru–Co coordination number compared to the RuCo nanoparticles. Numerous in-plane active alloy sites would remarkably facilitate the adsorption toward Li and CO 2 to accelerate the CO 2 RR reaction and improve the electron interactions with discharge products to enhance CO 2 ER reaction kinetics.…”
Section: Energy-related Applications Of Defective 2d Materialsmentioning
confidence: 97%
“…The heavy reliance of anthropogenic activities and industrialization on fossil fuels has dramatically increased the concentrations of atmospheric greenhouse gases, especially carbon dioxide (CO 2 ). Growing concern in the areas of global warming, extreme weather, climate change, and energy crisis is driving research on efficient CO 2 conversion to achieve carbon neutrality. Given the advantage of being able to be powered by renewable electricity, the electrocatalytic CO 2 reduction reaction (CO 2 RR) has emerged as one of the most promising and sustainable methods to convert CO 2 to valuable chemicals and fuels, especially highly valuable multicarbon (C 2+ ) products like ethylene (C 2 H 4 ), acetic acid (CH 3 COOH), ethanol (C 2 H 5 OH), and n-propanol ( n -C 3 H 7 OH). Among various types of electrocatalysts, copper (Cu)-based materials exhibited the most efficient electrochemical CO 2 conversion toward C 2+ products. To date, great effort, such as composition regulation, morphology adjustment, , defect control, strain modulation, , and phase engineering, has been devoted to modulating Cu-based electrocatalysts to boost the C 2+ production in CO 2 RR. However, due to the multiple electron-transfer processes and competitive reactions, it is still challenging to regulate the CO 2 RR reaction pathway toward C 2+ products. Meanwhile, most CO 2 RR electrocatalysts still demonstrate inferior activity, poor selectivity and low stability that limit the industry-scale applications. Hence, it is critically important to explore novel high-performance CO 2 RR electrocatalysts to efficiently convert CO 2 molecules to C 2+ products.…”
Section: Introductionmentioning
confidence: 99%